Effectiveness of PCSK9 inhibitors versus statins in type 2 diabetes and dyslipidemia: a propensity-matched study - Wu, Jheng-Yan; Lin, Yu Min; Hsu, Wan-Hsuan; Liu, Tinghui; Tsai, Ya-Wen; Huang, Po-Yu; Chuang, Min Hsiang; Yu, Tsung; Lai, Chih-Cheng (Frontiers in Endocrinology, 2025)
BackgroundProprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9is) exhibit promising lipid-lowering activity, but evidence regarding their effectiveness in real-world diabetic populations is limited.MethodsBased on TriNetX database, individuals T2D and dyslipidemia who were newly prescribed either a PCSK9 inhibitor or a statin between January 1, 2015, and April 30, 2025, were identified. After propensity score matching, 20,489 patients were classified into each treatment group. Primary endpoints were defined as a composite of all-cause mortality, major adverse cardiovascular events (MACE), and major adverse kidney events (MAKE) during the 5-year follow-up.ResultsPCSK9i use was associated with a reduced incidence of the primary outcome (hazard ratio [HR], 0.75; 95% CI, 0.70–0.81). Secondary outcomes also favored PCSK9i use, with reduced incidence of all-cause mortality (HR, 0.65; 95% CI, 0.60–0.705), MACE (HR, 0.83; 95% CI, 0.76–0.90), and MAKE (HR, 0.70; 95% CI, 0.61–0.81). Similar trends were observed for most of the subgroup and sensitivity tests. The association was significant for alirocumab and evolocumab, but not for inclisiran, likely due to limited sample size.ConclusionsAmong patients with T2D and dyslipidemia, PCSK9i use was associated with reduced incidences of cardiovascular and renal events and all-cause mortality compared to statin therapy. These findings support the promising role of PCSK9is in high-risk diabetic populations.